RANCANGAN SISTEM INFORMASI SUPPLY CHAIN MANAGEMENT PADA INDUSTRI MINUMAN: SUPPLY CHAIN MANAGEMENT INFORMATION SYSTEM DESIGN IN THE BEVERAGE INDUSTRY - Marwan (Engineering and Technology International Journal, 2020)
The beverage industry located in Medan City is a company engaged in the production of packaged drinks. In facing business competition, companies need an information system that is able to accommodate internal and external uncertainties in managing supply chain management in the company. Supply chain uncertainty in the company is caused by the uncertainty of product demand by customers and the lead time of delivery of raw materials by suppliers which results in uncertainty in the production process and ordering raw materials. This research was conducted to design a supply chain management information system application that can facilitate business processes with suppliers in the procurement of raw materials and the process of ordering products by customers to reduce the level of supply chain management uncertainty in the company. Applications designed to provide information to suppliers, customers and internal parties of the company. The information provided can make it easier for suppliers to control the inventory of raw materials at the company and the information will also make it easier for customers to order products offered by the company.